2010
DOI: 10.1111/j.1365-2869.2010.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Wrist actigraphic scoring for sleep laboratory patients: algorithm development

Abstract: SUMMARY Wrist actigraphy is employed increasingly in sleep research and clinical sleep medicine.Critical evaluation of the performance of new actigraphs and software is needed. Actigraphic sleep-wake estimation was compared with polysomnographic (PSG) scoring as the standard in a clinical sleep laboratory. A convenience sample of 116 patients undergoing clinical sleep recordings volunteered to participate. Actiwatch-L recordings were obtained from 98 participants, along with 18 recordings using the newer Spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 18 publications
1
63
0
Order By: Relevance
“…5 All of these devices are designed to measure light exposures and activity levels over extended periods of time while deployed in the field. One study characterized the Actiwatch Spectrum in terms of activity patterns and sleep quality, 6 another study used the device to record personal light exposures, 7 and one recent publication reported on its basic technical characteristics. 8 The technical characteristics of an earlier version of the Daysimeter have been published.…”
Section: Introductionmentioning
confidence: 99%
“…5 All of these devices are designed to measure light exposures and activity levels over extended periods of time while deployed in the field. One study characterized the Actiwatch Spectrum in terms of activity patterns and sleep quality, 6 another study used the device to record personal light exposures, 7 and one recent publication reported on its basic technical characteristics. 8 The technical characteristics of an earlier version of the Daysimeter have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Wrist actigraphs provide high sensitivity (i.e., accuracy in detecting sleep) particularly in normal sleepers (de Souza et al, 2003; Kripke et al, 2010). Yet some studies have raised concerns about the specificity (i.e., accuracy in detecting wakefulness) of actigraphy in some populations or devices (de Souza et al, 2003; Paquet, Kawinska, & Carrier, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that OSA in nonobese individuals is significantly associated with impaired glucose metabolism; however, OSA is not associated with abnormal glucose tolerance categories (2). That is to say, the association of OSA with glucose metabolism is different between obese and nonobese individuals.…”
Section: The Impact Of Obesity On the Association Between Obstructivementioning
confidence: 77%
“…We did use the medium threshold (40 counts per epoch) to differentiate wake from sleep. Prior studies have not found clear benefits in terms of agreement with polysomnography by using either a higher or lower threshold in adults (2,3). Although actigraphy is known to underestimate wake after sleep onset as a result of scoring of quiet wakefulness as sleep, there is little evidence to suggest this offset leads to systematic bias.…”
Section: The Impact Of Obesity On the Association Between Obstructivementioning
confidence: 99%